A Narrative Review of Outcome Studies for Residential and Partial Hospital‐based Treatment of Eating Disorders. (8th April 2016) - Friedman, Keren; Ramirez, Ana L.; Murray, Stuart B.; Anderson, Leslie K.; Cusack, Anne; Boutelle, Kerri N.; Kaye, Walter H.
Abstract: Objective: The objective of this study was to review the current eating disorders outcome literature after residential or partial hospitalization programme (PHP) treatment. Method: Articles were identified through a systematic search of PubMed and PsycINFO. Results: Twenty‐two PHP and six residential treatment studies reported response at discharge and tended to find improvement. Fewer studies (nine PHP and three residential) reported outcome at some interval after discharge from treatment. These tended to find sustained improvement. A substantial proportion of patients were lost to follow‐up, particularly for residential treatment. Only two follow‐up studies used controlled trials; both showed efficacy for PHP compared with inpatient treatment with regard to maintaining symptom remission. Conclusions: Improvement at discharge may not predict long‐term outcome. Long‐term follow‐up studies were confounded by high dropout rates. While higher levels of care may be essential for reversing malnutrition, there remains a lack of controlled trials showing long‐term efficacy, particularly for residential treatment settings. Copyright © 2016 John Wiley & Sons, Ltd and Eating Disorders Association.